The influence of project based learning on student's intrinsic learning motivation - Muslim Muslim; Hendra Dani Saputra; Muhammad Yasep Setiawan; Martias Martias; Muhammad Nasir (invotek, 2021)
The lack of total student involvement in the learning process is due to a lack of effort in finding information independently and not achieving active learning. The purpose of this study was to investigate the effect of intrinsic motivation on project-based learning in the automotive engineering education student workforce transfer system course. The method used was a quasi-experimental research design with a 2x2 factorial. The population used was students of the Automotive Engineering Department, Faculty of Engineering, Padang State University, 2020/2021 academic year. The results showed that students who applied project-based learning had higher learning outcomes than using conventional methods. This was based on the value of Fcount greater than Ftable, 7.866 > 3.34 at the 0.05 significance level. There is an interaction between learning methods and students' intrinsic motivation towards learning outcomes, this is evidenced by the value of Fcount is greater than Ftable, 7.602> 3.34 at the 0.05 significance level. There is a significant difference in student learning outcomes between project-based learning and conventional learning which has high intrinsic motivation. The final research result is that there is no significant difference in student learning outcomes between project-based learning and conventional learning which has low intrinsic motivation